2020
DOI: 10.1002/bmc.5000
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of five bioactive components of XiaoJin Capsule in normal and mammary gland hyperplasia rat plasma using LC–MS/MS and its application to a pharmacokinetic study

Abstract: XiaoJin Capsule (XJC) is a classic Traditional Chinese Medicine formula for clinical treatment of thyroid nodules, mammary gland hyperplasia and breast cancer. For the specification and rational application of XJC in the future, an accurate and specific LC–MS/MS method was developed and validated for quantitative determination of five components in rat plasma after oral administration of XJC. The collected plasma samples were extracted by protein precipitation with methanol–acetonitrile (1:3, v/v) mixture solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…As shown in Figure 2, there were double‐peaks in the concentration–time curves of glycyrrhetinic acid and glycyrrhetinic acid 3‐ O ‐glucuronide in normal and MGH model rats. The appearance of the double‐peak phenomenon might be related to physiological factors such as enterohepatic circulation and intragastric pH, as well as the disintegration, release and solubility of the compounds (Wang et al, 2021). Because the contents of other active ingredients in HHXYT were quite low except for glycyrrhetinic acid, and all components had typical strong hepatic metabolism characteristics, it was assumed that the pharmacological effects of HHXYT might mainly originate from glycyrrhetinic acid and the synergistic effect of many bioactive components with lower concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 2, there were double‐peaks in the concentration–time curves of glycyrrhetinic acid and glycyrrhetinic acid 3‐ O ‐glucuronide in normal and MGH model rats. The appearance of the double‐peak phenomenon might be related to physiological factors such as enterohepatic circulation and intragastric pH, as well as the disintegration, release and solubility of the compounds (Wang et al, 2021). Because the contents of other active ingredients in HHXYT were quite low except for glycyrrhetinic acid, and all components had typical strong hepatic metabolism characteristics, it was assumed that the pharmacological effects of HHXYT might mainly originate from glycyrrhetinic acid and the synergistic effect of many bioactive components with lower concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…23 In addition, Feng et al found that the Chinese herbal medicine D. opposita could exert therapeutic effects on myocardial ischemia by increasing the level of enzymatic and nonenzymatic antioxidants in vivo, reducing oxidative stress damage and metabolic markers related to intestinal flora metabolism by the UPLC−MS technique. 24 Metabonomics, a branch technology of systems biology, is a promising strategy to seize the metabolic alterations of endogenous metabolites through multivariate analysis and reveal the intervention mechanism of TCM. The metabonomics method will become an essential tool for uncovering disease pathogenesis and mechanisms of multicomponent medicinal effects.…”
Section: Introductionmentioning
confidence: 99%
“…Metabonomics, a branch technology of systems biology, is a promising strategy to seize the metabolic alterations of endogenous metabolites through multivariate analysis and reveal the intervention mechanism of TCM. The metabonomics method will become an essential tool for uncovering disease pathogenesis and mechanisms of multicomponent medicinal effects . Currently, the comprehensive research strategy of combining the integrity and systematic characteristics of network pharmacology with the high sensitivity of metabonomics has successfully revealed the mechanisms of TCM prescriptions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tang et al, (2023) established and validated a simple and sensitive ultrafast LC with MS/MS method for the determination of aconine, mesaconine, hypaconine, deoxyaconine, and fuziline in rat plasma to compare the pharmacokinetic characteristics of pure amino alcohol-diterpenoid alkaloids and Fuzi decoction. Wang et al, (2021) developed and validated an LC-MS/MS method for the quantitative determination of five components (aconine, songorine, neoline, 3-acetyl-11-keto-beta-boswellic acid, and 11-keto-beta-boswellic acid) of XiaoJin Capsule in rat plasma after oral administration. Dong et al, (2015) developed and validated a UPLC-MS/MS for measuring the concentration of songorine in rat plasma, and the method was successfully applied in a pharmacokinetic study after intravenous administration of 5.0 mg/kg songorine in rats.…”
mentioning
confidence: 99%